Translation Methods and Experience: A Comparative Analysis of Human Translation and Post-editing with Students and Professional Translators - Daems, Joke; Vandepitte, Sonia; Hartsuiker, Robert; Macken, Lieve (Meta, 2017)
While the benefits of using post-editing for technical texts have been more or less acknowledged, it remains unclear whether post-editing is a viable alternative to human translation for more general text types. In addition, we need a better understanding of both translation methods and how they are performed by students as well as professionals, so that pitfalls can be determined and translator training can be adapted accordingly. In this article, we aim to get a better understanding of the differences between human translation and post-editing for newspaper articles. Processes are registered by means of eye tracking and keystroke logging, which allows us to study translation speed, cognitive load, and the use of external resources. We also look at the final quality of the product as well as translators’ attitude towards both methods of translation. Studying these different aspects shows that both methods and groups are more similar than anticipated.